ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICING SAHAM PERDANA (Studi Kasus Pada Perusahaan Yang Melakukan IPO di BEI) (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the effect of underwriter reputation, return on assets, financial leverage, firm age, firm size, and earning per share on underpricing primeir stock of companies that have an Initial Public Offering on the Indonesia Stock Exchange. The study population were all listed companies on the Indonesia Stock Exchange and do an Initial Public Offering in the year of 2010 until 2013 as many as 100 companies, while the samples qualified as many as 73 companies. Based on the result of the study can be summarized as follows: (1) underwriter reputation have significant negative effect to underpricing, (2) return on assets have significant negative effect to underpricing, (3) financial leverage have not significant negative effect to underpricing, (4) firm age have not significant negative effect to underpricing, (5) firm size have significant negative effect to underpricing and (6) earning per share have not significant negative effect to underpricing.Keywords: Underpricing, Initial Public Offering, Underwriter Reputation, Return On Assets, Financial Leverage, Firm Age, Firm Size and Earning Per Share